Comprehensive analysis of challenges and two practical methods for protective coordination of distance relays in transmission lines connected to DFIG-based wind farms - Reza Shahbazzadeh; Mehrdad Tarafdar Hagh; Reza Ghanizadeh (Scientific Reports)
Abstract The increasing penetration of DFIG-based wind farms into high-voltage power systems has introduced new challenges for the coordination of distance protection relays. This study addresses how the distinct behavior of such generators, especially during the activation of the crowbar circuit under fault conditions, can lead to incorrect impedance estimation by distance relays, which may ultimately result in maloperation and unnecessary disconnection of wind farms. This outcome contradicts grid codes that mandate the continuous connection of wind farms during disturbances. To solve this issue, two innovative protection methods are proposed. The first method is based on time coordination between distance relays, where a small time delay is applied to the relay protecting the transmission line connected to the wind farm in order to prevent incorrect tripping. The second method combines this delay with the transmission of a simple low-bandwidth blocking signal, aiming to enhance reliability without full dependence on communication systems. Comprehensive evaluations demonstrate that the proposed methods significantly enhance the protection system’s performance and reliability. This research offers a practical and effective contribution toward improving protection coordination in power systems with high penetration of renewable energy sources.